2012
DOI: 10.1186/2191-219x-2-43
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular functional assessment in murine models of ischemic and dilated cardiomyopathy using [18 F]FDG-PET: comparison with cardiac MRI and monitoring erythropoietin therapy

Abstract: BackgroundWe performed an initial evaluation of non-invasive ECG-gated [18 F]FDG-positron emission tomography (FDG-PET) for serial measurements of left ventricular volumes and function in murine models of dilated (DCM) and ischemic cardiomyopathy (ICM), and then tested the effect of erythropoietin (EPO) treatment on DCM mice in a preliminary FDG-PET therapy monitoring study.MethodsMice developed DCM 8 weeks after injection with Coxsackievirus B3 (CVB3), whereas ICM was induced by ligation of the left anterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 31 publications
1
38
0
Order By: Relevance
“…Cardiomyocyte damages, leading to necrosis, edema, inflammatory cell infiltration, and fibrosis, were similar in both models. Similarly, 18 FDG-PET myocardial metabolism imaging revealed decreased myocardial viability, which was consistent with the findings reported by another study (Brunner et al, 2012). Similar to echocardiography, 18 FDG-PET imaging is a useful and minimally invasive evaluation method that can be used to detect pathological changes, offering the benefit of being useful for serial evaluations.…”
Section: Discussionsupporting
confidence: 81%
“…Cardiomyocyte damages, leading to necrosis, edema, inflammatory cell infiltration, and fibrosis, were similar in both models. Similarly, 18 FDG-PET myocardial metabolism imaging revealed decreased myocardial viability, which was consistent with the findings reported by another study (Brunner et al, 2012). Similar to echocardiography, 18 FDG-PET imaging is a useful and minimally invasive evaluation method that can be used to detect pathological changes, offering the benefit of being useful for serial evaluations.…”
Section: Discussionsupporting
confidence: 81%
“…HF is characterized by left ventricular (LV) remodeling and dilatation, with activation of a fetal gene program that triggers pathological changes in the myocardium associated with progressive dysfunction 55 . Tissue biopsy and cardiac radionuclide scan showed that there was no necrosis of cardiac muscle cells in the early stage of HF, but the degeneration, apoptosis and interstitial fibrosis of myocardial cells 56 57 58 59 60 61 . Therefore, most of the early HF patients firstly exhibit heart cavity expansion without obvious cardiac function insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The electrocardiogram (ECG)-gated FDG data were divided into 16 equal intervals and iteratively reconstructed using OSEM 3D (four iterations) and MAP (32 iterations), as previously described by our group. 9 All PET data were normalized and corrected for randoms, dead time and decay, and attenuation ( Figure 1). Right after the PET scan, the accuracy of the ECG trigger signals in the listmode data were verified using in-house software programmed in MATLAB (The Mathworks, Natick, MA) and in C programming language, and erroneous trigger events were removed as previously described.…”
Section: Administration Of Pthmentioning
confidence: 99%
“…An automated wall recognition algorithm was applied to delineate left ventricular contours, and the left ventricular ejection fraction (LVEF) was calculated as described by Brunner and colleagues. 9 The voxel size of the FDG images analyzed with QPS 2012 and QGS 2012 software packages had to be magnified by a factor of 10, as required for compatibility of smallanimal PET data with software designed for humans, as previously described. 12,13 Histologic Fluorescein Staining A separate group of mice was sacrificed on day 2 after LAD artery occlusion for histologic correlation of apoptosis and [ 68 Ga]annexin A5 uptake ex vivo (n 5 5 in the treatment group, n 5 5 in the control group).…”
Section: Administration Of Pthmentioning
confidence: 99%